Business group opportunism: the difference in real earnings management between parent firms and nonparent firms - Glenny Alawag (Asian Journal of Accounting Research, 2020)
This paper aims to understand real earnings management behavior in the context of a parent–subsidiary relationship. It explores the differences between business groups and firms that do not have controlled subsidiaries and provides potential explanations for any measured difference.The study uses the random-effects generalized least squares (GLS) estimation to find the difference between the real earnings management behavior of business groups, represented by the ultimate parent firms and the nonparent firms from 73 countries.The results show that ultimate parent firms have lower abnormal production costs and abnormal discretionary expenses than nonparent firms. In contrast, parent firms have higher abnormal cash flow from operations (CFO) than nonparent firms. The results are unexpected because abnormal production costs usually have a dominant direct relationship with abnormal CFO. The results indicate that business groups use a route different from manipulating production costs and discretionary expenses.The results reveal that parent firms use a route different from manipulating production costs and discretionary expenses. The results can be used to extend the discussion to specific business group cases, such as tracing the route or allocation of real earnings management (REM) pressure from a parent firm to its listed and private subsidiaries, and if the consolidation of minority voting rights and the transitivity of control affect the behavior in its subsidiaries.Instead of the degree of diversification or affiliation, this paper investigates REM behavior based on the parent firm's control of its subsidiaries. With this approach, the study argues that business groups prefer a route other than manipulating production costs and discretionary expenses. The results may redirect the attention of regulators to the activities of parent firms that need more policing.